Model Approach In Enforcement Of Perda No 5 Year 2017 About A No Smoking Area (Case Study Of Enforcement Within The Scope Of Opd East Kalimantan Province) - Ajisaka Bagas Satyanagara; Nabielah Fauzia; Nur Anisya Azlin; Wahyu Setiawan (Institute of Computer Science (IOCS), 2022)
Cigarettes have addictive properties whose use can cause non-communicable diseases (PTM) to active smokers and passive smokers. This research is entitled